A prática de diálogo em Paulo Freire na educação on-line, uma pesquisa bibliográfica digital: aproximações - Ramacciotti, Angélica Santos (2010)
This study aims to investigate the dialogue in construction of knowledge at graduation and post-graduation programs at the distance education modality in Brazil. To achieve the proposed goal, a qualitative approach with a dialectical perspective has been chosen for doing a digital bibliographical research. Using a methodic process to search through scientific papers published in open access online journals, between 2005 and 2009, with a total of eight publications selected. The systematical organization of all this information was elaborated based on the theoretical referential of Paulo Freire, starting from the concepts: listening , critical thinking , tolerance , respect for the student knowledge , epistemological curiosity , collective construction of knowledge and emancipation . The analysis and interpretation of the results demonstrate that the scientific production on the dialogical practices based on Paulo Freire for on-line education is starting to consolidate in the national academic scene. The collaborative dimension, spawning from the multiplicity of interchanges from on-line education evidences pedagogical proposals guided on the dialogue for collective knowledge construction. This way, new paths are open towards emancipatory curricula